Quality of ram spermatozoa separated with modified swim up method - Hossain, A; Islam, MM; Naznin, F; Ferdousi, RN; Bari, FY; Juyena, NS (Bangladesh Veterinarian, 2018)
Semen was collected from four rams, using artificial vagina and viability%, motility% and plasma membrane integrity% were measured. Fresh ejaculates (n = 32) were separated by modified swim-up separation using modified human tubal fluid medium. Four fractions of supernatant were collected at 15-minute intervals. The mean volume, mass activity, concentration, motility%, viability%, normal morphology and membrane integrity% (HOST +ve) of fresh semen were 1.0 ± 0.14, 4.1 ± 0.1 × 109 spermatozoa/ml, 85.0 ± 1.3, 89.4 ± 1.0, 85.5 ± 0.7, 84.7 ± 0.5 respectively. There was no significant (P>0.05) difference in fresh semen quality parameters between rams. The motility%, viability% and HOST +ve % of first, second, third and fourth fractions were 53.4 ± 0.5, 68.2 ± 0.3, 74.8 ± 0.3 and 65.5 ± 0.4; 55.5 ± 0.4, 66.2 ± 0.4, 74.5 ± 0.3 and 73.6 ± 0.3 and 66.7 ± 0.5, 66.8 ± 0.5, 65.2 ± 0.4 and 74.7 ± 0.5 respectively. The motility%, viability% and membrane integrity% of separated semen samples differed significantly (P<0.05) between four fractions. The mean motility% and viability% were significantly higher (P<0.05) in third fraction (74.8 ± 0.3%), whereas the mean HOST +ve% was significantly higher (P<0.05) in fourth fraction (74.7 ± 0.5). All quality parameters of separated spermatozoa were significantly (P<0.05) lower than that of fresh semen. The pregnancy rates were higher with fresh semen (71%) in comparison to that of separated sample (57%). Bangl. vet. 2016. Vol. 33, No. 2, 62-70